Factors influencing obtainment of master’s degree in Dentistry School of San Marcos University - Alvarado-Menacho, Sergio (2012)
The objective of this research was to determine the personal, academic and administrative factors that influence to obtain the academic degree of Dentristy Master in San Marcos National University for which we selected two groups of graduated without degree and graduated one. They were located personaly or by mail using a self-administered instrument. Was used the nonparametric test chi square. Relationship was found mainly with academics aspects as experience in the research area and the fact of being prepared for the development of a research project, have been responsible for a research project, having been participated as adviser or thesis project reviewer, having been published and carry out teaching, also administrative aspects due to the lack of administrative paperwork way and difficulties of acceptance from the institution where the work should be developed, finding no relation to the personal aspects.